2019
DOI: 10.3390/rs11172018
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the State-Of-The-Art Gridded Precipitation Products over Mountainous Terrain: A Regional Study over Austria

Abstract: During the last decade, satellite-based precipitation products have been believed to be a potential source for forcing inputs in hydro-meteorological and agricultural models, which are essential especially over the mountains area or in basins where ground gauges are generally sparse or nonexistent. This study comprehensively evaluates several newly released precipitation products, i.e., MSWEP-V2.2, IMERG-V05B, IMERG-V06A, IMERG-V05-RT, ERA5, and SM2RAIN-ASCAT, at daily and monthly time-scales over Austria. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 34 publications
9
38
0
Order By: Relevance
“…4 and 5). The same results were reported by Sharifi et al (2018) andO et al (2017) over the northeast and southeastern Austria, respectively. This should be noted that the Global Precipitation Climatology Centre (GPCC) dataset is used for adjusting the IMERG final run.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…4 and 5). The same results were reported by Sharifi et al (2018) andO et al (2017) over the northeast and southeastern Austria, respectively. This should be noted that the Global Precipitation Climatology Centre (GPCC) dataset is used for adjusting the IMERG final run.…”
Section: Discussionsupporting
confidence: 86%
“…POD ranges from 0 to 1 (the perfect score) and is utilized to estimate the hit rate. POD denotes the ratio of the number of precipitation events that are correctly detected by the SPPs to the total number of actual events (Sharifi et al 2018). FAR represents the fraction of falsely detected events (Xu et al 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in terms of maximum precipitation, the UKMO overestimated, while the satellite and other models showed underestimation over the Karkheh Basin during the second flood event. This might be due to high moisture in the atmosphere and the occurrence of small scale precipitation systems that were dominant during this event [23]. Additionally, from the median and the 25th and 75th percentiles of the box-plots, one can infer that the precipitation estimated by IMERG, followed by ECMWF, was more accurate than the other products in both basins, while the UKMO whiskers extended to the highest extreme data points in comparison to the other products.…”
Section: Mean Minimum and Maximum Basin Precipitationmentioning
confidence: 87%
“…However, IMERG real-time V05 performed substantially better than TMPA-3B42-real-time V7 and ERA5-HRES, particularly, in regions dominated by convective storms. In another study, Sharifi et al [23] examined the accuracy of six SPEs and gridded precipitation models against a dense network of 872 stations over Austria, in terms of extreme events and different altitude categories. They also found that the latest version of IMERG-V06A performed better than the other products (except MSWEP-2.2), which was consistent with the study results by Beck et al [22].…”
Section: Introductionmentioning
confidence: 99%